Selection, trade, and employment: The strategic use of subsidies - Hassan Molana; Catia Montagna (WWWforEurope, 2015)
We study how the interaction between economic openness and competitive selection affects the effectiveness of employment (and entry) subsidisation. Within a twocountry heterogeneous-firms model with endogenous labour supply, we find that optimal employment subsidies are always positive even though they can have pro- or anti-competitive effects on industry selection depending on whether the economy is open or not. We also find that selection effects resulting from international competition and fiscal externalities may imply that non-cooperative policies entail under-subsidisation of employment. Whilst always having procompetitive selection effects on the industry, entry subsidies are shown to be less effective in raising employment and welfare than employment subsidies.
Keywords: E22; E64; F12; F41; 330; optimal policy; employment subsidies; competitive selection; international trade